The Palgrave Handbook of New Directions in Kashmir Studies
XIX, 498 p. 3 illus., 2 illus. in color.
Keywords: The Palgrave Handbook of New Directions in Kashmir Studies provides a comprehensive, interdisciplinary and transregional perspective on the Kashmir dispute. Spanning South and Central Asia, Kashmir has been at the center of geopolitical conflicts and rivalries among India, Pakistan and China for decades, with members of heterogeneous local communities negotiating the complexities of regional state formations, national power assertions and geopolitical competitions. Taken together, the chapters in this handbook examine diverse people’s struggles to establish processes of democratic accountability in relation to the colonial-era state consolidations, postcolonial military occupations, interstate wars, intrastate armed conflicts and cold war and post-cold war politics that have shaped and transformed social and political identities in the region. Contributors chart out varied and bold new directions by attending to local constellations of situated knowledges and practices through which people living in different parts of the disputed region make sense of the conditions and contingencies of their political lives. The handbook further initiates a dialogue on the ways in which state power and border regimes have shaped scholarship and undermined the pursuit of shared intellectual and political projects across physical and epistemological boundaries. Haley Duschinski is Associate Professor of Anthropology and Faculty Affiliate of the Center for Law, Justice & Culture at Ohio University, USA. Mona Bhan is Associate Professor of Anthropology and Ford Maxwell Professor of South Asia at Syracuse University, USA. Cabeiri deBergh Robinson is Associate Professor of International Studies and Director of the Interdisciplinary Ph.D. Program in Near and Middle Eastern Studies at the University of Washington, USA.